Electrochemical Oxidative Cross‐Coupling of Pyrazolones and Diselenides to Construct C‐Se Bonds. Issue 2 (16th January 2023) - Lu, Fangling; Hu, Ling; Zhang, Jingyi; Feng, Yulin
Abstract: Organoselenium compounds are important molecules owing to their value in medicinal chemistry, material chemistry and biochemistry. The selenation of pharmaceutical molecules is a promising way to find new drugs. Herein, we introduced an electrochemical oxidative cross‐coupling of pyrazolones and diselenides without transition‐metal catalyst and external oxidant. Various pyrazolones and diselenides were compatible, generating the desired products in up to 86% yield. Preliminary mechanistic investigation suggested that a radical/radical cross‐coupling process might be involved in this transformation. This method provides a green and convenient route for directly installing a selenium moiety into bioactive pyrazolone derivatives, which possesses great application potential. Abstract : An efficient electrosynthesis of a series of 4‐seleno‐substituted pyrazolone analogues derivatives has been developed via electrochemical oxidative cross‐coupling of pyrazolones and diselenides under metal‐free and external oxidant free conditions. A broad range of pyrazolones and diselenides were compatible and the reaction could be conducted on gram scale with high reaction efficiency.